ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA TERHADAP TINGKAT LIKUIDITAS PT. KIRANA MEGANTARA TBK - MONTARIS SILAEN; LASMAN EDDY BACHTIAR; RIANTO . (LP2MTBM MAKARIOZ, 2021)
This research was conducted by the author to analyze the financial statements of PT. Kirana Megantara TBk. so that theycan know some things that are desired, namely (1) to see and find out where the sources of working capital owned by PT.Kirana Megantara, (2) Where the use of working capital is used by the company (3) Whether the company's managementcan maintain the stability of the company's liquidity level from year to year. Research using quantitative approach methodswith ex-post facto methods, the sample used in this study is financial statement data PT. Kirana Megantara for the last fiveconsecutive financial year periods were 2016, 2017, 2018, 2019 and 2020. The conclusions that can be obtained from thisstudy are (1) working capital sources obtained in 2017 amounting to Rp.2,694,725,781,000, - in 2018 Rp.51,166,187,000 in2019 Rp.2,480,789,325,000 and in 2020 Rp.915,190,713,000,- (2) while the payment Working capital in 2017Rp.981,436,636,000 in 2018 Rp.1,769,270,614,000 in 2019 Rp.620,013,527,000 and in 2020 Rp.1,946,297,115,000 then (3)the company's liquidity ratio level in 2016 amounted to .14.41%, in 2017 it was 7.30%, in 2018 it was 1.17%, in 2019 it was10.50% and in 2020 it was 1.17%.